Results and data for for the selection of optimum offshore wind farm locations for deployment - Mytilinou, Vera; Lozano-Minguez, Estivaliz; Kolios, Athanasios (Cranfield University, 2018)
Results and data acquired in the paper "A framework for the selection of optimum offshore wind farm locations for deployment"
Keywords: 'Multi-Criteria Decision Making'; 'Multi-Objective Optimisation'; 'TOPSIS'; 'Stochastic TOPSIS'; 'Life Cycle Cost analysis'; 'Power and Energy Systems Engineering (excl. Renewable Power)'; 'Renewable Power and Energy Systems Engineering (excl. Solar Cells)'